Students’ Attitudes towards English at Catholic University of Saint Thomas Medan - Karisma Erikson Tarigan (LingPoet: Journal of Linguistics and Literary Research, 2021)
This study about the language attitude of Students University Catholic of Saint Thomas Medan North Sumatera towards English. This research applied descriptive qualitative research design. The subject of this study was students at Unika Santo Thomas Medan about 100 students from four tribes (Karonese, Simalungun, Nias and Tobanese) in North Sumatera and 25 students taken from each tribe as sample. The purpose of this study was to find out the language attitude of Students University Catholic of Saint Thomas towards English. The results showed that there were 19 (76%) students of Karonese found English was interesting, 25 (100%) students of Nias, (94%) students of Simalungun, and 19 (76%) students of Tobanese found English was interesting.